Anthropometric And Biomotor Profile Analysis Of Water Ski And Wakeboard Athletes Of Dki Jakarta Province - Uzizatun Maslikah; Masnur Ali; Endy Safadilla; Haris Nugroho; Eko Sudarmanto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this study was to analyze the anthropometric and biomotor profiles of water skiers and wakeboard athletes in DKI Jakarta Province. The descriptive method uses a quantitative research type approach. The population and sample in this study were water skiers and wakeboard athletes as many as 25 male athletes. Data collection techniques used tests and measurements: (i) weight scales to measure body weight. bodyweight is measured using measuring body weight with a unit of kilograms; (ii) physical condition test; bend using the sit and reach test; core stability, namely athletes perform with 12 levels with perfect attitude, level 1 to level 12 where levels 1 and 12 for 30 seconds, level 2 to level 10 for 15 seconds, sit-ups and push-ups test athletes perform tests for 1 minute, limb explosive power did a standing long jump test, and endurance did a Multi-Stage Fitness Test (MFT). Data analysis uses quantitative descriptive analysis techniques, overall data analysis uses Microsoft Excel 2019. The results of this study can be concluded: anthropometry and physical condition are one of the important factors in determining athlete achievement, without exception for the DKI Jakarta Water Ski and Wakeboard Athletes.